Female Micro-Entrepreneurs and Social Networks: Diagnostic Analysis of the Influence of Social-Media Marketing Strategies on Brand Financial Performance - Jiménez-Zarco, Ana Isabel; Clemente-Almendros, José Antonio; González-González, Ines; Aracil-Jordá, Jorge (Frontiers in psychology, 2021)
The business world is facing a very complicated situation due to the COVID-19 pandemic. Small- and medium-sized companies (SMEs)-both in Spain and at the global level-are seeing their survival jeopardized by a fall in revenues. This scenario is aggravated in the case of micro-SMEs headed by female entrepreneurs. Accordingly, micro-SMEs, particularly those led by female entrepreneurs, need to reinvent themselves to overcome the current adversities that could lead to the destruction of their businesses and hence their jobs. One of the ways to do this is to take advantage of digital transformation. Therefore, the aim of this paper is to analyze which variables influence the financial results of female-led Spanish micro-SMEs when they carry out social marketing actions. For that purpose, an online survey was designed and analyzed using the "PROCESS" macro. Results show that social media marketing actions have significant effects on financial performance.
Keywords: women entrepreneurs; micro-SMEs; social media marketing; financial performance; digital transformation; JCR; Scopus